(untitled) (Justicia &Derecho, 2020)
The study will analyze the jurisprudence of the Supreme Court about with the non-renewal of contract employments, for this purpose, the jurisprudential precedents from 2015 to 2019, will be considered, evidencing the shortcomings and changes in the interpretative exercise of the judiciary.